2021
DOI: 10.1063/5.0067788
|View full text |Cite
|
Sign up to set email alerts
|

Semiflexible oligomers crystallize via a cooperative phase transition

Abstract: Semicrystalline polymers are ubiquitous, yet despite their fundamental and industrial importance, the theory of homogeneous nucleation from a melt remains a subject of debate. A key component of the controversy is that polymer crystallization is a non-equilibrium process, making it difficult to distinguish between effects that are purely kinetic and those that arise from the underlying thermodynamics. Due to computational cost constraints, simulations of polymer crystallization typically employ non-equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 104 publications
1
28
0
Order By: Relevance
“…Together with advanced sampling methods, MD simulations can also reveal the complex free energy landscapes for the phase transition. By equilibrium and nonequilibrium MD simulations, previous authors demonstrated the important roles of nematic order and precursors in crystal nucleation and suggested plausible multistage nucleation pathways. Indeed, previous simulation studies greatly enhanced our understanding of the thermodynamics of polymer crystallization. However, the role of polymer dynamics in crystallization kinetics remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with advanced sampling methods, MD simulations can also reveal the complex free energy landscapes for the phase transition. By equilibrium and nonequilibrium MD simulations, previous authors demonstrated the important roles of nematic order and precursors in crystal nucleation and suggested plausible multistage nucleation pathways. Indeed, previous simulation studies greatly enhanced our understanding of the thermodynamics of polymer crystallization. However, the role of polymer dynamics in crystallization kinetics remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, crystalline order prefers to grow in the less entangled and partially ordered regions. Still, because local orientational order can promote crystal nucleation, , the effect of entanglement on polymer nucleation is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Key factors that dictate phase behavior of athermal polymers include the presence of gaps in bond lengths, , volume fraction, , and chain stiffness, while chain length has a surprisingly minimal role. Simulations have clearly demonstrated that at the same volume fraction oligomers (of average length N = 12) or polymers deep in the polymeric regime ( N = 1000) crystallize with very similar mechanisms. , …”
Section: Introductionmentioning
confidence: 99%
“…In primary nucleation, the thermodynamic analysis by Kawak et al found a tandem growth of the global crystalline and nematic order near equilibrium, suggesting no equilibrium intermediate phase, while Zhang and Larson demonstrated a metastable nematic precursor to crystallization below an isotropic–nematic transition temperature predicted by theory. MD simulations of secondary nucleation by Bourque et al revealed a surface nucleation mechanism, wherein each new crystalline layer nucleates and spreads over the layer below it.…”
Section: Resultsmentioning
confidence: 99%
“…Milner found from a self-consistent field theory that nucleation from an intermediate nematic rotator phase is favored throughout the temperature range where crystal nucleation is observed. Kawak et al found from multiple Monte Carlo simulations that under near-equilibrium conditions the melt–crystal transition is smooth and cooperative, with nematic alignment and positional ordering occurring simultaneously. The phase transition behavior was speculated to differ under deeper quenches, based on their observation that the temperature-dependent polymer stiffness plays an important role in the cooperativity between nematic and crystalline order.…”
Section: Introductionmentioning
confidence: 99%